The Effect of Discovery Learning on Students' Essay Writing Skills - Martin Yuliani, Olvi; Sri Hartati, Yulia; Pebriani, Yulia (UIR PRESS, 2023)
The purpose of this study was to find out how the discovery learning paradigm affects the ability to write essays for class XI students of SMA Negeri 9 Padang. The methodology used in this research is explorative. One group participated in the pretest-posttest design selected for this investigation. The sample of this research was F4 class students of SMA Negeri 9 Padang, which consisted of 36 students. The educational tool consists of several sections, such as training modules, workbooks specifically designed to help students improve their essay writing skills, and performance tests to measure students' specific essay writing skills. By using the SPSS 25 for Windows program, data analysis was carried out to find out how the discovery learning paradigm influences student learning outcomes. This distribution is in accordance with the normal distribution, according to the findings of the normality test performed on the pretest data. The average value is calculated to be 60.94, and this result is based on the fact that the significance value (0.078 0.05) is greater than a predetermined threshold. The findings of the posttest data normality test confirm that the distribution is normal. The mean value of 77.77 and a significance level of 0.094, which is higher than the intended cutoff of 0.05, indicates this. The results of the significance test showed that the application of the discovery learning strategy had a statistically significant effect on the ability of class XI students of SMA Negeri 9 Padang in composing essays. This conclusion is reached using a significance level of 0.05 (p 0.05). Thus, it can be stated that the use of discovery learning methodology in eleventh grade students of SMA Negeri 9 Padang has a significant effect on their writing ability.